Low circulating Dickkopf-1 and its link with severity of spinal involvement in diffuse idiopathic skeletal hyperostosis. Issue 1 (7th September 2011) - Senolt, L; Hulejova, H; Krystufkova, O; Forejtova, S; Andres Cerezo, L; Gatterova, J; Pavelka, K; Vencovsky, J
Abstract : Objective: Dickkopf-1 (DKK-1) is an inhibitor of osteoblastogenesis, and its lower levels are linked to new bone formation. The aim of this study was therefore to explore serum levels of DKK-1 and to evaluate DKK-1's association with the severity of spinal involvement in diffuse idiopathic skeletal hyperostosis (DISH). Methods: Serum levels of total and functional DKK-1 and C-reactive protein (CRP) were measured in 37 patients with DISH and 22 healthy age and sex-matched controls. Plain radiographs of the cervical and thoracic spine were performed, and the diagnosis of DISH was defined using the Resnick criteria. Patients were divided into three groups based on spinal involvement. Bone mineral density (BMD) and bone turnover markers were evaluated in patients with DISH. Results: The levels of total serum DKK-1 were significantly lower in patients with DISH than in healthy controls (p<0.0001). Importantly, low serum levels of DKK-1 were associated with more severe spinal involvement in DISH, independent of age, sex, disease duration, CRP, bone turnover markers or BMD. However, these findings were less significant for functional DKK-1. Conclusion: These observations indicate that DKK-1 may play a significant role in bone formation during DISH.